Selected issues of IP telephony - Klimo, Martin; Kovacikova, Tatiana; Segec, Pavol (Communications - Scientific letters of the University of Zilina, 2004)
Technologies for transporting voice over networks based on IP protocol, known under various names, e.g., Voice Over IP (VoIP), Voice on the Net (VoN), IP telephony (below IP telephony), made a great progress in the last decade. IP telephony has become one of the most important and the most rapidly developing Internet technologies that is offering a technical as well as economical alternative to the existing telecommunication networks. The paper points three issues that from the authors’ point of view seem to be crucial for a wide deployment of IP telephony in European networks: Development and implementation of new IP telephony services based on the SIP (Session Initiation Protocol), Interworking between IP-based network signalling protocols and signalling protocols used in traditional SCNs (Switched Communication Networks) and the quality of voice transmission over IP networks. The paper also gives some examples of practical solutions of the problems mentioned above.